The Synthesis of Kynurenic Acid in Mammals: An Updated Kynurenine Aminotransferase Structural KATalogue - Rossi, Franca; Miggiano, Riccardo; Ferraris, Davide M.; Rizzi, Menico (Frontiers in Molecular Biosciences, 2019)
Kynurenic Acid (KYNA) is a bioactive compound generated along the kynurenine pathway for tryptophan degradation. In few decades, KYNA shifted from representing a poorly characterized by-product of tryptophan metabolism, to be considered a crucial player in many aspects of mammalian physiology, ranging from the control of glutamatergic and cholinergic synaptic transmission, to the participation to immunomodulation phenomena. The refreshed scientific attention payed to the study of KYNA homeostasis is in part justified by the discovery of selective and potent inhibitors of the human kynurenine aminotransferase II enzyme, mainly responsible for KYNA synthesis in the mammalian brain. Since abnormally high KYNA levels in the central nervous system have been associated with schizophrenia and cognitive impairment, such inhibitors promise the development of novel anti-psychotic and pro-cognitive drugs. We recapitulate here the structural information available on kynurenine aminotransferases (KATs) as the result of global efforts aimed at providing the X-ray crystallography-based structural description of the full complement of the mammalian isozymes. These investigations allowed the identification of KATs peculiar features that could be deployed in the search of isozyme-specific inhibitors. Together with the description of biochemical assays able to discriminate among the activity of each single KAT in complex samples, this wealth of knowledge has driven, and continues to foster, the identification of brain penetrant, small molecules to be used to attenuate KYNA synthesis, i.e. molecules that should be capable of lowering KYNA levels when required, without exposing the brain to a potentially harmful withdrawal of this neuroprotective compound.